PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM PERANCANGAN KONSEP VISUAL LIVE COMMERCE BACKGROUND PADA BRAND HP INDONESIA - Maulina Dwi Handayani; Leonard Dharmawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Artificial Intelligence (AI) has transformed creative processes in the design industry, including live commerce visual production. This study aims to analyze the use of AI in designing live commerce backgrounds for HP Indonesia at Live & Go. A qualitative descriptive approach was employed using observation, interviews, documentation, and literature review. Data were analyzed using the Miles and Huberman model and Wallas’ creative process theory. The findings show that AI supports idea exploration, generates visual alternatives, and accelerates design development. However, AI cannot fully replace designers due to its limitations in understanding design principles, brand visual identity, and visual communication needs. Therefore, AI serves as a supporting tool that enhances designers’ creativity and productivity.Keywords: Artificial Intelligence, live commerce background, graphic design, design workflow, brand visual identity.